HOSPITALITY ON THE FARM: THE DEVELOPMENT OF A SYSTEMS MODEL OF FARM TOURISM - KIDD, JEFFREY (ASEAN Journal on Hospitality and Tourism, 2011)
In this paper the author discusses hospitality in the form of farm tourism, and uses the basics of systems theory to identify the various stakeholders involved in farm tourism. The main factors that are identified that have relevance to farm tourism are those that can be grouped under the following headings: physical, competitive, demographic and socio-cultural, economic, technological and politico-legal influences; together with the inputs (supply) of farm tourism, composed mainly of farmers; and the output (demand) side of the model, which comprises the services provided to guests, and the experiences guests have when visiting farms. This information is then used to create a model which is essentially a review of contemporary understanding of farm tourism, and to briefly discuss the various influences in the model, as well as their interrelationships.